Pengaruh Model Pembelajaran Index Card Match Terhadap Penguasaan Mufradat Siswa Madrasah Diniyah Bahrul Ulum Coban Blimbing Wonorejo - Syarifuddin; Lailatun Nimah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The problem that exists in the Madrasah Diniyah Bahrul Ulum Coban Blimbing is the idea that there are still numerous students think that learning is a boring and monotonous lesson that results in students becoming less proficient in the material, especially in mastering vocabulary. Researchers tried to solve the problem using an index card match learning model. This study aims to determine the influence of the student's knowledge of vocabulary of the index card match learning model of Madrasah Diniyah Bahrul Ulum Coban Blimbing Wonorejo. This type of study uses experimental quantitative trials with a pre-trial and post-trial design. Observation, testing, and publishing will be used as survey methodologies.This study can be known using normally distributed data, with a value of 0.546 > 0.05 on the initial test or pre-test and a value of 0.209 > 0.05 on the final test or post-test. And the paired sample t test averaged 69.75 and the deviation was 19,226 while the post-test average was 74.00 and the deviation was 20,170. In light of all this, it can be stated that the use of the Index Card Match Learning Model have improved improving the mastery of vocabulary of Madrasah Diniyah Bahrul Ulum students.